Green Synthesis of Copper Oxide Nanoparticles Using Mentha (Mint) Leaves Characterization and Its Antimicrobial Properties with Phytochemicals Screening - Baral, Janaki; Pokharel, Neena; Dhungana, Sujan; Tiwari, Laxmi; Khadka, Devendra; Pokhrel, Megh Raj; Poudel, Bhoj Raj (Journal of Nepal Chemical Society, 2025)
This study demonstrates the synthesis of copper oxide nanoparticles from the leaf extract of Mentha as a natural reducing and stabilizing agent. The synthesized nanoparticles were characterized by UV-visible spectroscopy, Fourier-transform infrared (FTIR) and X-ray diffraction (XRD). UV-vis shows an absorption peak at 275 nm associated with plasmon surface vibrations. FTIR analysis confirmed the reduction and stabilization of CuO nanoparticles, while XRD revealed the monoclinic structure with an average particle size of 19.08 nm, calculated using Debye-Scherrer’s equation. Phytochemical analysis of the methanolic extract identified active components biomolecules such as flavonoids, saponins, and terpenoids, which contribute as reducing and capping agents in nanoparticles. The nanoparticles demonstrated strong antimicrobial activity against Staphylococcus aureus (Gram-positive), Escherichia coli (Gram-negative), and Candida albicans (fungus).